Are there alternatives to bankruptcy? A study of small business distress in Spain - Miguel García-Posada; Juan S. Mora Sanguinetti (SERIEs - Journal of the Spanish Economic Association, 2014)
Small businesses, the majority of Spanish firms, rarely file for formal bankruptcy when dealing with financial distress. This is why business bankruptcy rates in Spain are among the lowest in the world, even during the current economic crisis. To explain this fact we present the following hypothesis. Filing for bankruptcy in Spain is very costly for both small firms and their creditors. Due to this, the capital structure of micro firms is biased towards mortgage loans, as it allows them to avoid bankruptcy by carrying out debt enforcement via mortgage foreclosures, which are cheaper procedures than bankruptcy, in case of financial distress. The empirical tests of our hypothesis consist of comparing the observed choices (choice of capital structure, choice between bankruptcy and mortgage) of Spanish firms with those of firms from countries (France and the UK) where their bankruptcy systems are more efficient and their laws do not incentivise them to bias their capital structure towards mortgage loans. Our findings corroborate the proposed hypothesis. As bankruptcy procedures and mortgage foreclosures are not perfect substitutes - i.e., they do not suit well the same type of firms - the underutilization of one of them - reflected in low bankruptcy rates - may lead to efficiency losses.
Keywords: G33; G21; K0; 330; Bankruptcy; Mortgage; Insolvency